2013
DOI: 10.1371/journal.pone.0067877
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Compliance and Sway Properties of Tree Branches Used by the Sumatran Orangutan (Pongo abelii)

Abstract: The tropical arboreal environment is a mechanically complex and varied habitat. Arboreal inhabitants must adapt to changes in the compliance and stability of supports when moving around trees. Because the orangutan is the largest habitual arboreal inhabitant, it is unusually susceptible to branch compliance and stability and therefore represents a unique animal model to help investigate how animals cope with the mechanical heterogeneity of the tropical canopy. The aim of this study was to investigate how chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 32 publications
4
32
0
Order By: Relevance
“…They construct a “nest” or sleeping platform . Great apes build a new sleeping platform each night, specifically selecting trees for their firm, stable, and resilient biomechanical properties . In contrast, the lesser apes, the gibbons, do not build sleeping platforms; instead, they follow the ancestral primate pattern of sleeping on tree branches, typically lying or sitting on what is available without altering their local environment .…”
Section: Allometric Scaling and Ecology Of Sleep Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…They construct a “nest” or sleeping platform . Great apes build a new sleeping platform each night, specifically selecting trees for their firm, stable, and resilient biomechanical properties . In contrast, the lesser apes, the gibbons, do not build sleeping platforms; instead, they follow the ancestral primate pattern of sleeping on tree branches, typically lying or sitting on what is available without altering their local environment .…”
Section: Allometric Scaling and Ecology Of Sleep Sitesmentioning
confidence: 99%
“…70,71 Great apes build a new sleeping platform each night, specifically selecting trees for their firm, stable, and resilient biomechanical properties. [72][73][74] In contrast, the lesser apes, the gibbons, do not build sleeping platforms; instead, they follow the ancestral primate pattern of sleeping on tree branches, typically lying or sitting on what is available without altering their local environment. 75 Arboreal platforms provide several benefits to sleepers, including keeping individuals out of range of terrestrial predators, [76][77][78] repelling blood-sucking arthropods and/or masking individual insect-attracting odors, 64,[79][80][81] providing added insulation to keep warm, 65,81 and providing a more stable and secure environment.…”
Section: Box 1 Phylogenetic Outlier Analysismentioning
confidence: 99%
“…It has been shown that chimpanzee sleeping platform complexity increases with the height of a sleep site [Samson, 2012]. Folia Primatol 2015;86:187-202 DOI: 10.1159/000381056 198 Samson/Shumaker Ancrenaz et al [2004] observed that terrestrial predators coupled with highly fragmented ecology resulted in a Sabah orangutan preference for tall trees and the highest of sleeping platform sites of all the apes; additionally, van Casteren et al [2012van Casteren et al [ , 2013 have reported that wild orangutans are characterized by a sophisticated understanding of the engineering properties of nest construction and biomechanical properties of compliance and sway of arboreally placed sleeping platforms. Since gorillas are the only other ape with comparable sexual dimorphism, and their more continuous habitat enables them to sleep habitually on the ground or low in the canopy if necessary [Tutin et al, 1995], it may be that male orangutans make highly complex sleeping platforms due to the adaptive necessity of a massive-bodied animal sleeping at great heights.…”
Section: Discussionmentioning
confidence: 99%
“…Systematic behavioral and mechanical studies on wild orangutan sleeping platform construction have increased our understanding of wild great ape sleep ecology [Russon, 2007;Rayadin and Saitoh, 2009;van Casteren et al, 2012van Casteren et al, , 2013], yet no such counterpart for captive studies has been published to date. The goal of this study was to provide a more systematic characterization of captive ape sleep-related behavior by documenting pre-sleep (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We constructed a force gauge apparatus similar to that described by van Casteren, Venkataraman, Ennos, and Lucas (; van Casteren et al, ) to measure substrate compliance (i.e., displacement divided by force; reciprocal of stiffness; Figure ). Our apparatus included a force gauge (500 N capacity) fixed to a three‐legged aluminum stand.…”
Section: Methodsmentioning
confidence: 99%